Diffusion Tensor Imaging in Lissencephaly - Rollins, Nancy (AJNR Am J Neuroradiol, 2005)
Summary: Lissencephaly is a rare brain malformation characterized histologically by arrested neuronal migration such that the brain resembles that of a fetus before 23–24 weeks gestation. We studied a neonate with lissencephaly by using diffusion tensor imaging and suggest the dysplastic densely cellular layer IV is visible as a band of anisotropic diffusion. Fiber tracking showed lack of connectivity between the cortex and deep white matter and an abnormal limbic system.